Rapeseed napin and cruciferin are readily digested by poultry - Kasprzak, M.M.; Houdijk, J.G.M.; Liddell, S.; Davis, K.; Olukosi, O.A.; Kightley, S.; White, G.A.; Wiseman, J. (Wiley, 2017)
Rapeseed proteins have been considered as being poorly digestible in the gut of non-ruminants. The aim of the study was to assess the digestibility of napin and cruciferin in ileal digesta of broiler chickens, testing sixteen samples of rapeseed co-products with protein levels ranging from 293 g/kg to 560 g/kg dry matter. Each sample was included into a semi-synthetic diet at a rate of 500 g/kg and evaluated with broiler chickens in a randomised design. Dietary and ileal digesta proteins were extracted and identified by gel-based liquid chromatography–tandem mass spectrometry (LC-MS/MS). Three isomers of napin (a 2S albumin) and nine cruciferins (an 11S globulin) were identified in the rapeseed co-products, whereas six endogenous enzymes such as trypsin (I-P1, II-P29), chymotrypsin (elastase and precursor), carboxypeptidase B and α-amylase were found in the ileal digesta. It is concluded that as none of the rapeseed proteins were detected in the ileal digesta, rapeseed proteins can be readily digested by broiler chickens, irrespective of the protein content in the diet.